Service Quality: An empirical study of Expectations versus Perceptions in Retail Banking - Arora, Usha; Vashishat , Bhavna (Gyan Management Journal, 2011)
This paper examines and measures the quality of services provided by Indian commercial banks in India. The expectations and perceptions of borrowers regarding service quality dimensions are composed and service quality of banks is measured regarding credit schemes. In this study, total service quality is measured in five dimensions with the help of a structured questionnaire filled by borrowers of banks. The SERVQUAL instrumen_t has been used for the measurement of service quality in banks. The study brings out a gap between the expectations and perceptions of borrowers regarding service quality in banks.
Keywords: Service Quality; SERVQUAL; Banking Services; Commercial Banks; Cranach 'sAlpha.